Analysis of Students' Mathematical Problem-Solving Abilities - Jaenudin, Sopian; Aminah, Mimih; Yusuf, Yusfita (Jurnal Cendekia : Jurnal Pendidikan Matematika, 2024)
This study aims to analyze the mathematical problem-solving ability of grade VII students on ratio materials using Polya problem-solving steps. This study uses a qualitative descriptive approach involving 28 grade VII students of one of the State Junior High Schools in Sumedang Regency as participants. The instrument employed consisists of three descriptive test questions designed to assess students’ abilities in understanding problems, planning solutions, executing those plans, and evaluating the outcomes of their problem-solving processes. The results of the study show that students with high abilities are able to solve each problem well, while students with agile skills experience difficulties at almost all stages, especially in understanding problems and developing solution plans. Mistakes that are often found in students with low ability include a lack of understanding of the concept of ratios and an inability to organize relevant information.